2017
DOI: 10.1016/j.cub.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The Jellyfish Cassiopea Exhibits a Sleep-like State

Abstract: SUMMARY Do all animals sleep? Sleep has been observed in many vertebrates, and there is a growing body of evidence for sleep-like states in arthropods and nematodes [1–5]. Here we show that sleep is also present in Cnidaria [6–8], an earlier branching metazoan lineage. Cnidaria, along with Ctenophora, are the first metazoan phyla to evolve tissue-level organization and differentiated cell types, such as neurons and muscle [9–15]. In Cnidaria, neurons are organized into a non-centralized radially symmetric nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
180
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(191 citation statements)
references
References 44 publications
8
180
0
3
Order By: Relevance
“…In animals, the sleep–wake cycle is arguably the most conspicuous, ubiquitous, and important circadian rhythm. All animals—even simple animals, including jellyfish (Nath et al., ) and flatworms (Omond et al., )—sleep. Sleep can have important benefits for development and learning (Derégnaucourt, Mitra, Fehér, Pytte, & Tchernichovski, ; Kayser, Yue, & Sehgal, ), attention, motivation and emotional reactivity (Van Dongen, Maislin, Mullington, & Dinges, ), hand–eye coordination (Dawson & Reid, ), memory (Diekelmann & Born, ), immune function (Imeri & Opp, ), neurological waste clearance (Xie et al., ), and energy homeostasis (Schmidt, ; Schmidt, Swang, Hamilton, & Best, ).…”
Section: Introductionmentioning
confidence: 99%
“…In animals, the sleep–wake cycle is arguably the most conspicuous, ubiquitous, and important circadian rhythm. All animals—even simple animals, including jellyfish (Nath et al., ) and flatworms (Omond et al., )—sleep. Sleep can have important benefits for development and learning (Derégnaucourt, Mitra, Fehér, Pytte, & Tchernichovski, ; Kayser, Yue, & Sehgal, ), attention, motivation and emotional reactivity (Van Dongen, Maislin, Mullington, & Dinges, ), hand–eye coordination (Dawson & Reid, ), memory (Diekelmann & Born, ), immune function (Imeri & Opp, ), neurological waste clearance (Xie et al., ), and energy homeostasis (Schmidt, ; Schmidt, Swang, Hamilton, & Best, ).…”
Section: Introductionmentioning
confidence: 99%
“…Animals ranging from jellyfish to humans display a homeostatic rebound following sleep deprivation [6,47]. Here we describe a functional and molecular mechanism underlying resilience to starvation-induced sleep loss.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is one example of a neural state that dramatically alters an animal's sensorimotor transformations [22,23]. Studies of sleep across the phylogenetic tree have shown that sensory systems transition to a reduced activity state that leads to a decreased animal response to external stimuli [24][25][26][27][28]. Additionally, sleep and wakefulness have been shown to correspond with distinct patterns of neural activity in humans [22,23], cats [29], rodents [23], and fruit flies [30,31].…”
Section: Introductionmentioning
confidence: 99%